$L^∞$ Error Estimates of Nonconforming Finite Elements for the Biharmonic Equation (Journal of Computational Mathematics, 1993)
The paper considers the $L^∞$ convergence for nonconforming finite elements, such as Morley element, Adini element and De Veubeke element, solving the boundary value problem of the bihamonic equation. The nearly optimal order $L^∞$ estimates are given.